(untitled) (Veterinary Science, 2019)
Milk fever or hypocalcemia still is one of the most prevalent metabolic diseases as a consequence of the continued selection for the productivity of the dairy cattle. The present manuscript reviews the new aspect of the disease, mineral interactions, treatments and preventive measurement under either cattle in confinement or on pasture